A granular analysis of service delivery for surgical system strengthening: Application of the Lancet indicators for policy development in Colombia - Andres Fernando Gomez Samper; Gabriel E. Herrera-Almario; David Tulloch; Daniela Blanco; Linda Lucia Cardoso; Ricardo Elias Nunez Rocha; Roshni Rajan; Vicente Gracias; Joseph S. Hanna (Elsevier, 2022)
Summary: Background: The Lancet Commission on Global Surgery (LCoGS) surgical indicators have given the surgical community metrics for objectively characterizing the disparity in access to surgical healthcare. However, aggregate national statistics lack sufficient specificity to inform strengthening plans at the community level. We performed a second-stage analysis of Colombian surgical system service delivery to inform the development of resource- and context-sensitive interventions to inform a revision of the Decennial Public Health Plan for access inequity resolution. Methods: Data from the year 2016 to inform total operative volume (TOV) and 30-day non-risk adjusted peri-operative mortality (POMR) were collected from the Colombian national health information system. TOV and POMR were sub-characterized by demographics, urgency, service line, disease pathology and facility location. Findings: In 2016, aggregate national mortality was 0·87%, while mortality attributable to elective and emergency surgery was 0·73% and 1·30%, respectively. The elderly experienced a 5·6-fold higher mortality, with 4·2% undergoing an operation within 30 days of dying. Individuals undergoing hepatobiliary, thoracic, cardiac, and neurosurgical operations experienced the highest mortality rates while obstetrics, general surgery, orthopaedics, and urology performed the largest procedure volume. Finally, analysis of operation and service line specific POMR reveals opportunities for improvement. Interpretation: This granular second-stage analysis provides actionable data which is fundamental to the development of resource and context-sensitive interventions to address gaps and inequities in surgical system service delivery. Furthermore, this analysis validates the modeling underlying development of the LCoGS indicators. These data will inform the assessment of implementation priorities and revision of the Colombian Decennial Public Health Plan. Funding: None.